Sexual reproduction of human fungal pathogens - Heitman, Joseph; Carter, Dee A.; Dyer, Paul S.; Soll, David R. (Cold Spring Harbor Laboratory Press, 2014)
We review here recent advances in our understanding of sexual reproduction in fungal pathogens that commonly infect humans, including Candida albicans, Cryptococcus neoformans/gattii, and Aspergillus fumigatus. Where appropriate or relevant, we introduce findings on other species associated with human infections. In particular, we focus on rapid advances involving genetic, genomic, and population genetic approaches that have reshaped our view of how fungal pathogens evolve. Rather than being asexual, mitotic, and largely clonal, as was thought to be prevalent as recently as a decade ago, we now appreciate that the vast majority of pathogenic fungi have retained extant sexual, or parasexual, cycles. In some examples, sexual and parasexual unions of pathogenic fungi involve closely related individuals, generating diversity in the population but with more restricted recombination than expected from fertile, sexual, outcrossing and recombining populations. In other cases, species and isolates participate in global outcrossing populations with the capacity for considerable levels of gene flow. These findings illustrate general principles of eukaryotic pathogen emergence with relevance for other fungi, parasitic eukaryotic pathogens, and both unicellular and multicellular eukaryotic organisms.